2017
DOI: 10.1111/jcal.12198
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking students' conceptualizations through haptic feedback

Abstract: While it is clear that the use of computer simulations has a beneficial effect on learning when compared to instruction without computer simulations, there is still room for improvement to fully realize their benefits for learning. Haptic technologies can fulfill the educational potential of computer simulations by adding the sense of touch. Visuohaptic simulations may not only help students visualize these concepts, but they may also have the capability of enriching the learning experience and enhancing reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…However, after engaging with embodied experiences via sequenced VH interactions (combination of touch sensor and visual cues), they increased the percentage of correct and complete statements. These results show similarities with previous studies conducted by Jones et al Magana and Balachandran , Magana et al , Hallman et al , and Reiner .…”
Section: Discussion and Implications For Teaching And Learningsupporting
confidence: 90%
See 4 more Smart Citations
“…However, after engaging with embodied experiences via sequenced VH interactions (combination of touch sensor and visual cues), they increased the percentage of correct and complete statements. These results show similarities with previous studies conducted by Jones et al Magana and Balachandran , Magana et al , Hallman et al , and Reiner .…”
Section: Discussion and Implications For Teaching And Learningsupporting
confidence: 90%
“…Previous literature which studied students’ learning with embodied learning experiences demonstrated a positive effect on conceptual learning . Even though the argument about adding haptic feedback to visual manipulation is not better than having visual manipulation alone , the results from previous studies conducted by our research team showed that haptic feedback has great potential to improve student learning of force‐related concepts .…”
Section: Discussion and Implications For Teaching And Learningmentioning
confidence: 98%
See 3 more Smart Citations